Creatinine Trends to Detect Ibuprofen-Related Maturational Adverse Drug Events in Neonatal Life: A Simulation Study for the ELBW Newborn - Tamara van Donge; Karel Allegaert; Karel Allegaert; Karel Allegaert; Marc Pfister; Anne Smits; Anne Smits; John van den Anker; John van den Anker; John van den Anker (Frontiers Media S.A., 2021)
Background: Recognizing a change in serum creatinine concentrations is useful to detect a renal adverse drug reaction signal. Assessing and characterizing the nephrotoxic side-effects of drugs in extremely low birth weight (ELBW, ≤1000 g) neonates remain challenging due to the high variability in creatinine in this population. This study aims to investigate and quantify the impact of ibuprofen treatment on kidney function, reflected by serum creatinine.Method: A recently developed dynamical model for serum creatinine was used to simulate creatinine profiles for typical, reference ELBW neonates with varying gestational and postnatal ages whilst being exposed to ibuprofen treatment.Results: The increase of serum creatinine concentrations due to ibuprofen treatment is most apparent during the first week of life. The difference in serum creatinine values between ibuprofen-exposed vs. non-exposed neonates decreases with increasing postnatal age, independent of gestational age.Conclusion: The difference in serum creatinine concentrations between ibuprofen-exposed vs. non-exposed neonates decreases with postnatal age, indicating an increased clearing capacity and resulting in a weak ibuprofen-related adverse drug reaction signal beyond early neonatal life.